1992
DOI: 10.3109/00365529209165421
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Sucralfate and Ranitidine, Compared with Sucralfate Monotherapy, in Patients with Peptic Reflux Esophagitis

Abstract: A double-blind, multicenter, randomized study was performed in 75 patients with endoscopically documented reflux esophagitis. Patients were randomly given 1 g sucralfate four times a day or the combination of sucralfate three times a day and 300 mg ranitidine after dinnertime. Endoscopy was performed at the beginning of the study, after 8 weeks, and, if, the reflux esophagitis was not healed, after 16 weeks. Four patients had to be excluded from evaluation; 71 patients could therefore be evaluated. Both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Optimal medical management for oesophagitis has not been determined in human or veterinary medicine. Controlled clinical trials in humans are limited and often conflicting (Vermeijden et al 1992, Vigneri et al 1995. In this series, medical management was instituted on a case by case basis at the discretion of the clinician.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal medical management for oesophagitis has not been determined in human or veterinary medicine. Controlled clinical trials in humans are limited and often conflicting (Vermeijden et al 1992, Vigneri et al 1995. In this series, medical management was instituted on a case by case basis at the discretion of the clinician.…”
Section: Discussionmentioning
confidence: 99%
“…The expected experience of standard sucralfate for symptomatic relief of eGERD is that 7 days would be insufficient time to provide symptomatic relief on par with standard of care therapeutic options. Specifically, Vermeijden et al [39] reported the best known outcomes for sucralfate in the treatment of eGERD. Using standard sucralfate, patients required 56 days to achieve 80% symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, pre-polymerized sucralfate required only 7 days for 80% symptomatic relief. Additionally, Vermeijden et al [39] observed that in 56 days, 4 grams daily of standard sucralfate (or 224 grams) was required to achieve a healing rate of 68%. In this trial using 3 grams per day for 7 days (or 21 grams) of pre-polymerized sucralfate suspension barrier, 80% complete healing and 20% partial healing was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…21 It is even as effective as H2RAs in improving GERD symptoms and healing erosive esophagitis. 22,23 Third, the other component of AlbisD, bismuth, can inhibit certain bacterial activities. However, its inhibitory effect on bacteria such as H. pylori may not have played an important role in improving the symptoms of the study patients, because GERD or NERD are not closely associated with H. pylori status.…”
Section: Discussionmentioning
confidence: 99%